Micro RNA based MSC EV engineering: Targeting the BMP2 cascade for bone repair - Huang, Chun-Chieh; Kang, Miya; Leung, Kasey; Lu, Yu; Shirazi, Sajjad; Gajendrareddy, Praveen; Ravindran, Sriram (Frontiers in Cell and Developmental Biology, 2023)
Abstract: Mesenchymal stem cell derived extracellular vesicles (MSC EVs) possess excellent immunomodulatory and therapeutic properties. While beneficial, from a translational perspective, EVs with consistent functionality and target specificity are required to achieve the goals of precision medicine and tissue engineering. Prior research has identified that the miRNA composition of MSC EVs contributes significantly towards EV functionality. In this study, we hypothesized that MSC EV functionality can be rendered pathway-specific using a miRNA-based EV engineering approach. To test this hypothesis, we utilized bone repair as a model system and the BMP2 signaling cascade as the targeted pathway. We engineered MSC EVs to possess increased levels of miR-424, a potentiator of the BMP2 signaling cascade. We evaluated the physical and functional characteristics of these EVs and their enhanced ability to trigger the osteogenic differentiation of naïve MSC in vitro and facilitate bone repair in vivo. Results indicated that the engineered EVs retained their EV characteristics and endocytic functionality and demonstrated enhanced osteoinductive function by activating SMAD1/5/8 phosphorylation and MSC differentiation in vitro and enhanced bone repair in vivo. Furthermore, the inherent immunomodulatory properties of the MSC EVs remained unaltered. These results serve as a proof-of-concept for miRNA-based EV engineering approaches for regenerative medicine applications.